Unknown Input Observer untuk Robust Detection Sinyal Kesalahan terhadap Disturbance Menggunakan LMI - Samiadji Herdjunanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Implementation of time scheduled maintenance is not suitable if it is applied for systems with many varieties of heavy workload and harsh environment, since on that condition components degrade earlier than those under normal condition. Therefore, it has been shifted to condition-based maintenance (CBM). One important aspect, among others, toward successfull implementation of CBM method is fault signal detection which is robust against disturbance. The proposed solution of the problem is to use Unknown Input Observer (UIO) where its parameters are chosen so that UIO can be used for fault signal detection which is robust against disturbance. The parameter values of UIO are calculated using linear matrix inequality (LMI) derived from Lyapunov stability requirement. To demonstrate the effectiveness of the proposed solution, simulation is performed on a separately-excited DC motor where its load has a step change and time-varying change. The result shows that a fault signal as a function of nonlinear state can be detected using UIO which is robust against both step and time-varying load of the DC motor.